Numbers Write, Wipe and learn ! - Abraham, Darcie; Hemsley, Eleanor; Meredith, Samantha (Cottage Farm, UK Igloo Books Ltd, 2024)
Flip over the pages of this wipe-clean easel for a fun way to learn to count from 1-20. With dotted lines to follow and clear activities to complete, this is the perfect first step for learning numbers
Arithmetic Notions
Keywords: Mathematics